Integrated stochastic life cycle benefit cost analysis of hydronically-heated apron pavement system. (1st July 2019) - Nahvi, Ali; Pyrialakou, V. Dimitra; Anand, Pritha; Sadati, S.M. Sajed; Gkritza, Konstantina; Ceylan, Halil; Cetin, Kristen; Kim, Sunghwan; Gopalakrishnan, Kasthurirangan; Taylor, Peter C.
Abstract: Transportation infrastructure and operations are greatly impacted by ice and snow, adding enormous costs to the American economy. Because of their sustainability benefits, heated-pavement systems (HPS) continue to gain attention as a potential alternative to conventional snow removal operations, and the main goal of this paper is to assess the economic feasibility of hydronically-heated pavements systems (HHPS), one type of heated pavements, for use at apron areas of commercial airports. Both benefits and expenses associated with use of HHPS for snow and ice removal were identified and quantified in monetary terms using a stochastic economic analysis method, and a sensitivity analysis approach was used to determine particular variables that significantly influence overall economic viability of HHPS. The findings suggest that, despite high capital costs, HHPS use at airports might be economically feasible. The results from the sensitivity analysis indicate that airport size, in the context of number of aircraft operations, strongly affects the benefit-cost ratio of HHPS use.